Opportunities of combination therapy in reproductive age patients with bacterial vaginosis combined with vulvovaginal candidiasis - I. V. Savelieva; E. A. Bukharova; E. G. Galyanskaya; N. V. Nosova; P. V. Davydov (Акушерство, гинекология и репродукция, 2025)
Aim: to assess the effectiveness of combination therapy in reproductive age patients with mixed vaginitis.Materials and Methods. A retrospective analysis of the therapeutic effectiveness for mixed vaginitis in 158 patients aged 18 to 45 years was carried out. For treatment, the drugs Gainomax (standard dose – thioconazole 100 mg, tinidazole 150 mg in the form of a suppository) and Gainomax plus (standard dose – thioconazole 200 mg, tinidazole 300 mg, lidocaine 100 mg in the form of a suppository) were used for 3 days. The criteria for treatment effectiveness were disappearance of clinical symptoms and normalization of laboratory parameters.Results. Clinical and laboratory efficacy of therapy reached 95.6 %. Lack of therapeutic effectiveness presented as persistent complaints from patients was recorded in 7 out of 158 (4.4 %) of patients, at the same time, the normalization of vaginal pH was established (pH = 4.1 ± 0.4), the Lactobacilli count increased up to 107 ± 2.8 CFU/cm3, eradication of other opportunistic bacteria and fungi Candida occurred. No side effects were reported while assessing drug safety and tolerability.Conclusion. Therapy combining thioconazole and tinidazole in treatment of patients with mixed vaginitis demonstrated high effectiveness.